Electrosurgery or laser for benign prostatic enlargement: trumpcard or pitfalls. Issue 5 (September 2021) - Pallauf, Maximilian; Herrmann, Thomas; Oswald, David; Törzsök, Peter; Deininger, Susanne; Lusuardi, Lukas
Abstract : Purpose of review: To summarize and comment on publications of the last 2 years in the field of endoscopic surgery for benign prostatic enlargement, focusing on similarities and differences of laser and electrosurgery. Recent findings: Because of good hemostasis and safety, invasive endoscopic surgery has evolved to a choice of treatment for vulnerable patients with ongoing antithrombotic medication and in same-day surgery. Recent publications show a good perioperative course and no deterioration in the postoperative outcome. Furthermore, alterations to the original surgical techniques of resection, enucleation, and vaporization have increased the preservation rate for antegrade ejaculation, advancing them to an appealing choice of treatment for sexually active men. Favorable outcomes can be achieved in both laser and electrosurgery. Only the choice of the surgical technique determines the outcome. Summary: Various invasive endoscopic surgical techniques are available, offering different advantages and disadvantages for the patient. All of them can be performed with laser and electrosurgery. Therefore, focusing on the proper choice of surgical technique instead of the energy source will guarantee the patient to benefit most.